Etude des systèmes de mis à la terre du point neutre dans l’environnement industriel - Bouhamed, Med Tamime; Necib, Med Khalil (Université Echahid Hama Lakhdar- Eloued -Algérie, 2013)
The aim of this thesis project is to investigate and understand the different grounding schemes used in an industrial environment by identifying the type of faults, analyzing the changes affecting the power Systems with respect to faults currents and voltages. Five different grounding schemes will be used to test and analyze the three power System models constructed. The five grounding schemes found in the industries are solidly grounded, ungrounded, high-resistance grounding, low-resistance grounding, low inductance grounding, and resonant grounding. Four types of System faults (manly single-line to ground, line to line, three-phase balanced and double-line to ground) will be emulated on the power System models that are constructed based on each of the five grounding methods used and the results will be compiled and analyzes.هناك طرق مختلفة لربط الحيادي مع للأرض في وسط صناعي، وفي معظم الحالات يكون حيادي مع الأرض مباشرة، حيادي منعزل، حيادي بمقاومة صغيرة وكبيرة، حيادي متوازن، كل طريقة لها خصائص، مزايا وعيوب. والهدف الرئيسي من هذا البحث هو معرفة خصائص كل طريقة لربط الحيادي وبعد ذلك استخدام برنامج محاكاة لمعالجة كل طريقة، ومقارنة النتائج لإيجاد طريقة لربط الحيادي مع للأرض.
Catalogue d'Eléctromécanique Industrielleمذكرات ليسانس تخصص الكترو